2019
DOI: 10.15405/epsbs.2019.04.48
|View full text |Cite
|
Sign up to set email alerts
|

Resource-Saving Technologies Of Cultivation Of Grain In The Conditions Of Novgorod Region

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…B. Tiranov Selection and peer-review under (Table 03) showed that the lowest specific energy intensity of production of a ton of fodder units was obtained in perennial grasses − clover of the first year of use and clover-andtimothy grass mixture of the second year of use -0.9-1.0 kJ. Then in an ascending order -the grains of winter rye -1.6-1.8 kJ; barley -2.0-2.6 kJ; oats -3.3-4.0 kJ (Tiranova & Tiranov, 2005;Kirkorova, Lipnitsky, Tiranova, & Tiranov, 2019). 2.3; 1.9 kJ respectively was obtained in all crop rotations.…”
Section: Resultsmentioning
confidence: 99%
“…B. Tiranov Selection and peer-review under (Table 03) showed that the lowest specific energy intensity of production of a ton of fodder units was obtained in perennial grasses − clover of the first year of use and clover-andtimothy grass mixture of the second year of use -0.9-1.0 kJ. Then in an ascending order -the grains of winter rye -1.6-1.8 kJ; barley -2.0-2.6 kJ; oats -3.3-4.0 kJ (Tiranova & Tiranov, 2005;Kirkorova, Lipnitsky, Tiranova, & Tiranov, 2019). 2.3; 1.9 kJ respectively was obtained in all crop rotations.…”
Section: Resultsmentioning
confidence: 99%